Extracellular vesicles: lipids as key components of their biogenesis and functions - Record, Michel; Silvente-Poirot, Sandrine; Poirot, Marc; Wakelam, MichaelJ.O. (Journal of lipid research, 2018)
Intercellular communication has been known for decades to involve either direct contact between cells or to operate via circulating molecules, such as cytokines, growth factors, or lipid mediators. During the last decade, we have begun to appreciate the increasing importance of intercellular communication mediated by extracellular vesicles released by viable cells either from plasma membrane shedding (microvesicles, also named microparticles) or from an intracellular compartment (exosomes). Exosomes and microvesicles circulate in all biological fluids and can trigger biological responses at a distance. Their effects include a large variety of biological processes, such as immune surveillance, modification of tumor microenvironment, or regulation of inflammation. Extracellular vesicles can carry a large array of active molecules, including lipid mediators, such as eicosanoids, proteins, and nucleic acids, able to modify the phenotype of receiving cells. This review will highlight the role of the various lipidic pathways involved in the biogenesis and functions of microvesicles and exosomes.